Performance of Dye-Sensitized Solar Cells with (PVDF-HFP)-KI-EC-PC Electrolyte and Different Dye Materials - M. M. Noor; M. H. Buraidah; S. N. F. Yusuf; M. A. Careem; S. R. Majid; A. K. Arof (International Journal of Photoenergy)
A plasticized polymer electrolyte system composed of PVDF-HFP, potassium iodide (KI), and equal weight of ethylene carbonate (EC) and propylene carbonate (PC) has been used in a dye-sensitized solar cell (DSSC). The electrolyte with the composition 40 wt. % PVDF-HFP-10 wt. % KI-50 wt. % (EC + PC) exhibits the highest room temperature ionic conductivity of 1.10 × 10−3 S cm−1. A small amount of iodine crystal of about 10 wt. % of KI was added to the electrolyte in the liquid state to provide the redox couple for DSSC operation. The polymer electrolyte films were prepared by the solvent casting method. The DSSCs were fabricated with the electrolyte film sandwiched between a TiO2/dye photoelectrode and a Pt-counter electrode and characterized under 100 mW cm−2 white light. The DSSC performance with different dyes such as Ruthenizer 535 (N3), anthocyanin, chlorophyll, and a mixture of anthocyanin and chlorophyll (v/v=1) has been compared. The DSSC with Ruthenizer 535 (N3) dye exhibits the best performance with a short-circuit current density of 8.16 mA cm−2, open-circuit voltage of 0.76 V, fill factor of 0.35, and photoconversion efficiency of 2.2%.